40 lat praw miejskich Władysławowa reż. Marek Kramarczyk, scen. Krystian Sagola. - Kramarczyk, Marek; Sagola, Krystian; Szenkin, Michał (Nasza TV, 2005)
Historia miasta Władysławowa oraz prawie 100 archiwalnych zdjęć od 1920 r.